2021
DOI: 10.1016/j.neuroimage.2021.118075
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the organization and dynamics of the posterior medial network during movie watching

Abstract: Brain regions within a posterior medial network (PMN) are characterized by sensitivity to episodic tasks, and they also demonstrate strong functional connectivity as part of the default network. Despite its cohesive structure, delineating the intranetwork organization and functional diversity of the PMN is crucial for understanding its contributions to multidimensional event cognition. Here, we probed functional connectivity of the PMN during movie watching to identify its pattern of connections and subnetwork… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 77 publications
(118 reference statements)
2
25
0
Order By: Relevance
“…Additionally, edge time series likely relate to the dynamic information that can be computed at the edge level via the Multiplication of Temporal Derivatives method, which has demonstrated increased temporal sensitivity to simulated and task-evoked changes in connectivity ( Shine et al, 2015 ). There remains much to be explored regarding the networked edge dynamics, including the ongoing topology these dynamics form ( Betzel et al, 2021 ) and the cofluctuation patterns that might evolve intrinsically ( Lindquist, Xu, Nebel, & Caffo, 2014 ) or evoked during experimental manipulations ( Cooper, Kurkela, Davis, & Ritchey, 2021 ; Rosenthal, Sporns, & Avidan, 2017 ).…”
Section: Edges In Communication and Brain Dynamicsmentioning
confidence: 99%
“…Additionally, edge time series likely relate to the dynamic information that can be computed at the edge level via the Multiplication of Temporal Derivatives method, which has demonstrated increased temporal sensitivity to simulated and task-evoked changes in connectivity ( Shine et al, 2015 ). There remains much to be explored regarding the networked edge dynamics, including the ongoing topology these dynamics form ( Betzel et al, 2021 ) and the cofluctuation patterns that might evolve intrinsically ( Lindquist, Xu, Nebel, & Caffo, 2014 ) or evoked during experimental manipulations ( Cooper, Kurkela, Davis, & Ritchey, 2021 ; Rosenthal, Sporns, & Avidan, 2017 ).…”
Section: Edges In Communication and Brain Dynamicsmentioning
confidence: 99%
“…For example, the stationary functional connectivity between the supramarginal gyrus and posterior cingulate gyrus was close to zero, while the windowed dynamic connectivity showed highly consistent fluctuations. To date, only handful of studies have examined dynamic connectivity during movie watching (Cooper et al, 2021;Freitas et al, 2020;Simony and Chang, 2020). It is still largely unknown how the spatial pattern is modulated by different movie contents, and how dynamic connectivity is spatially distributed.…”
Section: Introductionmentioning
confidence: 99%
“…The neocortex, however, is not a homogeneous collection of regions and specific networks of neocortical regions are thought to play a role in representing event models and connect with the hippocampus. Analyses of cortical networks with fMRI have indicated that the hippocampus shows high functional connectivity with a "Medial Temporal Network" (MTN) and 3 subnetworks of the DMN (Andrews-Hanna et al, 2010;Barnett et al, 2021;Cooper et al, 2021;Gordon et al, 2020)-the "Posterior Medial Network" (PMN), "Anterior Temporal Network (ATN)", and the "Medial Prefrontal Network" (MPN). These networks can be differentiated based on multivariate representations during memory-guided decision making (Barnett et al, 2021), task activation (DiNicola et al, 2020), and functional connectivity patterns (Barnett et al, 2021;Braga et al, 2019;Cooper et al, 2021;Gordon et al, 2020).…”
mentioning
confidence: 99%
“…Analyses of cortical networks with fMRI have indicated that the hippocampus shows high functional connectivity with a "Medial Temporal Network" (MTN) and 3 subnetworks of the DMN (Andrews-Hanna et al, 2010;Barnett et al, 2021;Cooper et al, 2021;Gordon et al, 2020)-the "Posterior Medial Network" (PMN), "Anterior Temporal Network (ATN)", and the "Medial Prefrontal Network" (MPN). These networks can be differentiated based on multivariate representations during memory-guided decision making (Barnett et al, 2021), task activation (DiNicola et al, 2020), and functional connectivity patterns (Barnett et al, 2021;Braga et al, 2019;Cooper et al, 2021;Gordon et al, 2020). While these networks show reliable connectivity with the hippocampus, it is unclear how their interactions with the hippocampus support encoding and whether this support is amplified at event boundaries.…”
mentioning
confidence: 99%